VERIFICATION OF THE MODEL "INNOVATION OF EXPERIMENTAL PREPARATION OF PHYSICS STUDENTS" IN THE FORM OF E-LEARNING - HORVÁTHOVÁ, Daniela (Trends in education, 2011)
In the submitted contribution we are demonstrating the creation of a new e-learning educational programme and our experience with this implementation. This program was created as a part of the subject called Introduction to the experimental physics. It's included in the winter term schedules of the first year a study of physics.
Keywords: E-learning; LMS Moodle; interactive educational text.